NUCLEAR MEDICINE INTERDISCIPLINARY INTEGRATION OF THE SCIENCE OF TECHNOLOGIES ON THE TOPIC OF THE EFFECTS OF IONIZING RADIATION ON LIVING ORGANISMS - Ergashev Askar Jong'oboyevich; Khudoyberdiyeva GulsanamNasimjon kizi (Modern American Journals, 2025)
This article provides detailed information about ionizing radiation, its types, current use in medicine, its harmful effects on the human body, and reveals the features of using interdisciplinary integration in its teaching.
Keywords: Medicine, ionizing radiation, diagnostics, treatment, educational practice, scope, radiation, radiation dose.